2017
DOI: 10.1007/s11060-017-2379-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers in glioma

Abstract: Gliomas are the most malignant and aggressive form of brain tumors, and account for the majority of brain cancer related deaths. Malignant gliomas, including glioblastoma are treated with radiation and temozolomide, with only a minor benefit in survival time. A number of advances have been made in understanding glioma biology, including the discovery of cancer stem cells, termed glioma stem cells (GSC). Some of these advances include the delineation of molecular hetereogeneity both between tumors from differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
251
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(258 citation statements)
references
References 62 publications
4
251
0
3
Order By: Relevance
“…3D). This was also highlighted by differential expression of putative marker genes for GBM subtypes 18 across patient samples ( Supplementary Fig. 2C).…”
Section: Scrna-seq Reveals Transcriptional Heterogeneity Between Tumomentioning
confidence: 78%
“…3D). This was also highlighted by differential expression of putative marker genes for GBM subtypes 18 across patient samples ( Supplementary Fig. 2C).…”
Section: Scrna-seq Reveals Transcriptional Heterogeneity Between Tumomentioning
confidence: 78%
“…2,3 Owing to the indistinct symptoms and lack of an effective diagnostic method for early detection, patients with GC are typically diagnosed at an advanced stage and have a dismal prognosis. 5,6 Taking this into consideration, it is necessary to seek more effective biological markers for the diagnosis and treatment of GC. 5,6 Taking this into consideration, it is necessary to seek more effective biological markers for the diagnosis and treatment of GC.…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, more well-known molecular markers including MGMT, IDH, EGFR, p53, Rb, and RAF are identified in gliomas. 16 Here, we reported that PTPN2 was upregulated in glioma cells. PTPN2 silence could significantly inhibit glioma progression.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, a number of circulating biomarkers have been identified in glioma patients . In addition, more well‐known molecular markers including MGMT, IDH, EGFR, p53, Rb, and RAF are identified in gliomas . Here, we reported that PTPN2 was upregulated in glioma cells.…”
Section: Discussionmentioning
confidence: 99%